Perubahan Sosial Masyarakat Desa Akibat Penggunaan Sumber Air Bersama Perusahaan Daerah Air Minum (PDAM) - Yunita, Desi; Nurwati, Nunung; Gunawan, Wahju (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2020)
The water source in the Perhutani forest area is the main water source for the village community in Sumedang Regency West Java. At present, the same source is also used by the Sumedang Regency water company to meet the water needs of urban communities. This article describes the social changes that have occurred in rural communities as a result of the shared use of water resources from the Perhutani Forest. This article is based on qualitative research with a case study approach. Data collection techniques used were observation, interviews, and questionnaires. It was found that there have been social changes in forest-edge communities. The change is clearly seen in the changing pattern of planting and community agricultural commodities. Furthermore, it was found that changes also occurred in the mode of production (infrastructure) which was marked by the shift of control of the water source to the water company (PDAM), the changes in the mode of production directly affect changes in the structure of the forest village community which is mainly seen from changes in community livelihoods due to changes in agricultural patterns and systems in the community. Changes to the structure can also be seen from the formation of the existing water user structure at the RW level to regulate household water allocation and distribution.